"To float, to hide, to disappear": The Hacker in The Circle. - Mandel, Naomi (Mosaic: An Interdisciplinary Critical Journal, 2021)
Reading Dave Eggers's The Circle through the figure of the computer hacker, this essay reflects on the history of hacking, hacking's evolving relationship with embodiment, and the implications of this relationship for the representation of technology in literature.